Discovering the Potential of Natural Antioxidants in Age-Related Macular Degeneration: A Review - Kah-Hui Wong; Hui-Yin Nam; Sze-Yuen Lew; Murali Naidu; Pamela David; Tengku Ain Kamalden; Siti Nurma Hanim Hadie; Lee-Wei Lim (MDPI AG, 2022)
Age-related macular degeneration (AMD) is a multifactorial disease associated with anatomical changes in the inner retina. Despite tremendous advances in clinical care, there is currently no cure for AMD. This review aims to evaluate the published literature on the therapeutic roles of natural antioxidants in AMD. A literature search of PubMed, Web of Science and Google Scholar for peer-reviewed articles published between 1 January 2011 and 31 October 2021 was undertaken. A total of 82 preclinical and 18 clinical studies were eligible for inclusion in this review. We identified active compounds, carotenoids, extracts and polysaccharides, flavonoids, formulations, vitamins and whole foods with potential therapeutic roles in AMD. We evaluated the integral cellular signaling pathways including the activation of antioxidant pathways and angiogenesis pathways orchestrating their mode of action. In conclusion, we examined the therapeutic roles of natural antioxidants in AMD which warrant further study for application in clinical practice. Our current understanding is that natural antioxidants have the potential to improve or halt the progression of AMD, and tailoring therapeutics to the specific disease stages may be the key to preventing irreversible vision loss.